Pengaruh Perasan Daun Pandan Wangi (Pandanus amaryllifolius Roxb) Terhadap Shigella dysentriae - Diah Ariana (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2017)
ABSTRACTDysentriae Shigella is a bacterial species of shigella that occurs in tropical countries, these bacteria are pathogenic gut bacteria are commonly known to cause dysentery. Dysentery is an infection that causes sores that cause ulcers limited dicolon characterized by symptoms known as dysentery syndrome. In user of trimatoprim sulfametaksazol can cause or accelerate the onset of megaloblastosis, leocopenia, or trombostopenia. In regular use, this combination appears to show little toxicity, approximately 75% of these adverse effects involving the skin. ‘Pandan wangi’ (pandanus amaryllifolius roxb) is one of the plants that can be used as a natural antibiotic against shigella dysentriae infection because the content of fragrant pandan leaves include flavonoids, alkaloids, saponins and tannins.This type of research is experimental, while the goal is to determine the effect  of ‘pandan wangi’ leaf (pandanus amaryllifolius roxb) juice on shigella dysentriae. Consisting of 7 concentrations and four repetitions. Using dilution method by observing the growth of bacteria shigella dysentriae on ‘pandan wangi’ leaf juice that is characterized by the colonies grown on media Mac Conkey (MC).Data analysis uses Anova with an error or a = 5%. The advanced test uses Tukkey test, Honestly Significant Difference (HSD). After doing the research, the optimal concentration of juice of ‘pandan wangi’ (pandanus amaryllifolius roxb) leaves can inhibit shigella dysentriae is 25% and can kill shigella dysentriae from concentration of 50%. The final conclusion is that there is the effect of ‘pandan wangi’ (pandanus amaryllifolius roxb) leaf juice on shigella dysentriae. Keywords: Pandanus amaryllifolius Roxb leaves, shigella dysentriae.